Bacterial genotype and clinical outcomes in solid organ transplant recipients with Staphylococcus aureus bacteremia. Issue 6 (16th December 2021) - Eichenberger, Emily M; Ruffin, Felicia; Sharma‐Kuinkel, Batu; Dagher, Michael; Park, Lawrence; Kohler, Celia; Sinclair, Matthew R; Maskarinec, Stacey A; Fowler, Vance G
Abstract: Introduction: Outcomes from Staphylococcus aureus bacteremia (SAB) in solid organ transplant (SOT) recipients are poorly understood. Methods: This is a prospective cohort study comparing the bacterial genotype and clinical outcomes of SAB among SOT and non‐transplant (non‐SOT) recipients from 2005 to 2019. Each subject's initial S. aureus bloodstream isolate was genotyped using spa typing and assigned to a clonal complex. Results: A total of 103 SOT and 1783 non‐SOT recipients with SAB were included. Bacterial genotype did not differ significantly between SOT and non‐SOT recipients ( p  = .4673), including the proportion of SAB caused by USA300 (13.2% vs. 16.0%, p  = .2680). Transplant status was not significantly associated with 90‐day mortality (18.4% vs. 29.5%; adjusted odds ratio [aOR] 0.74; 95% confidence interval [CI]: 0.44, 1.25), but was associated with increased risk for septic shock (50.0% vs. 21.8%; aOR 2.31; 95% CI: 1.48, 3.61) and acute respiratory distress syndrome (21.4% vs. 13.7%; aOR 2.03; 95% CI: 1.22, 3.37), and a significantly lower risk of metastatic complications (33.0% vs. 45.5%; aOR 0.49; 95% CI: 0.32, 0.76). No association was found between bacterial genotype and 90‐day mortality ( p  = .6222) or septic shock ( p  = .5080) in SOT recipients with SAB. Conclusions: SOT recipients with SAB do not experience greater mortality than non‐SOT recipients. The genotype of S. aureus bloodstream isolates in SOT recipients is similar to that of non‐SOT recipients, and does not appear to be an important determinant of outcome in SOT recipients with SAB.